Safety and efficacy of nivolumab in challenging subgroups with advanced melanoma who progressed on or after ipilimumab treatment: A single-arm, open-label, phase II study (CheckMate 172). (November 2019) - Schadendorf, Dirk; Ascierto, Paolo A.; Haanen, John; Espinosa, Enrique; Demidov, Lev; Garbe, Claus; Guida, Michele; Lorigan, Paul; Chiarion-Sileni, Vanna; Gogas, Helen; Maio, Michele; Fierro, Maria Teresa; et al.
Abstract: Background: Limited data are available on nivolumab in challenging subgroups with advanced melanoma. We report outcomes of nivolumab after prior ipilimumab in patients who are typically excluded from clinical trials. Patients and methods: In this phase II, single-arm, open-label, multicentre study (CheckMate 172), patients with advanced melanoma who progressed on or after ipilimumab received nivolumab 3 mg/kg, every 2 weeks for up to 2 years. The primary objective was incidence of grade ≥3, treatment-related select adverse events (AEs). Results: At a minimum follow-up of 18 months, grade ≥3 treatment-related select AEs with the most variation across subgroups were diarrhoea and colitis (1.1% [n = 11] and 0.3% [n = 3] for the total population [n = 1008]; 0.6% [n = 1] and 0.6% [n = 1] for patients with an asymptomatic central nervous system [CNS] metastasis [n = 165; 16.4%]; 4.5% [n = 3] and 3.0% [n = 2] for patients with an Eastern Cooperative Oncology Group performance status [ECOG PS] of 2 [n = 66; 6.5%]; 2.4% [n = 2] and 0% for those who experienced a grade 3/4 immune-related AE [irAE] with prior ipilimumab [n = 84; 8.3%]; and 0% and 0% for autoimmune disease [n = 25; 2.5%], respectively). Median overall survival was 21.4 months in the total population and was 11.6, 2.4, 21.5, and 18.6 months in patients with a CNS metastasis, ECOG PS 2, a grade 3/4 irAE with prior ipilimumab, and autoimmune disease, respectively. Conclusions: In this large, phase II clinical trial of patients with advanced melanoma who progressed on or after ipilimumab, nivolumab demonstrated a safety profile consistent with that of prior clinical trials. ClinicalTrials.gov ID: NCT02156804 . Highlights: The safety profile of nivolumab was consistent with that observed in prior studies. Adverse events with the most variation across subgroups were diarrhoea and colitis. Median overall survival was lowest in patients with poor performance status.